2016
DOI: 10.1016/j.jpsychires.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma, BDNF Val66Met and subclinical psychotic experiences. Attempt at replication in two independent samples

Abstract: Childhood trauma exposure is a robust environmental risk factor for psychosis. However, not all exposed individuals develop psychotic symptoms later in life. The Brain-derived neurotrophic factor (BDNF) Val66Met polymorphism (rs6265) has been suggested to moderate the psychosis-inducing effects of childhood trauma in clinical and nonclinical samples. Our study aimed to explore the interaction effect between childhood trauma and the BDNF Val66Met polymorphism on subclinical psychotic experiences (PEs). This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 78 publications
0
15
0
1
Order By: Relevance
“…According to our review, 12 studies have evaluated interactions between exposure to childhood trauma and genetic factors in schizophrenia spectrum disorders [ 21 , 22 , 31 , 33 36 , 38 , 41 , 42 , 45 , 123 ]. The vast majority of studies suggest significant interactions between genetic underpinnings and exposure to childhood adversities, stressful life events or recent stressors and genetic factors, with only three studies reporting negative findings [ 25 , 35 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to our review, 12 studies have evaluated interactions between exposure to childhood trauma and genetic factors in schizophrenia spectrum disorders [ 21 , 22 , 31 , 33 36 , 38 , 41 , 42 , 45 , 123 ]. The vast majority of studies suggest significant interactions between genetic underpinnings and exposure to childhood adversities, stressful life events or recent stressors and genetic factors, with only three studies reporting negative findings [ 25 , 35 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In three studies [ 21 , 33 , 123 ], interactions between a history of childhood trauma and the BDNF Val66Met polymorphism were addressed, showing positive findings. Aas et al [ 33 ] found an additive effect of the BDNF 66Met allele and a history of childhood trauma on reduced levels of BDNF mRNA as well as CA2/3 and CA4 subfield volumes of dentate gyrus in the hippocampus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BDNF Val66Met polymorphism has been reported to interact with early life stress; thus, Val carriers with childhood trauma are more susceptible to the occurrence of subclinical psychotic experiences ( de Castro-Catala et al, 2016 ). Another study in subjects with the schizophrenia spectrum or bipolar disorder demonstrated that Met carriers with high levels of childhood trauma have significantly low levels of blood BDNF mRNA and decreased CA2/3 and CA4 subfield areas in the dentate gyrus ( Aas et al, 2014 ).…”
Section: Interaction Between Bdnf Val66met Polymormentioning
confidence: 99%
“…In this sense, a limited but increasing number of GxE studies have shown that certain single nucleotide polymorphisms (SNPs) interact with distal or proximal stress to heighten risk for psychotic experiences (PEs; e.g., 11). For example, it has been shown that the brain‐derived neurotrophic factor ( BDNF ) Val66Met polymorphism moderates the psychosis‐inducing effects of distal 12, 13 and momentary stress 14. However, scarce research has examined the interaction of genetic variants with both distal and proximal stress within the same study.…”
Section: Introductionmentioning
confidence: 99%